Novel delay-partitioning stabilization approach for networked control system via Wirtinger-based inequalities. (March 2016) - Li, Zhichen; Bai, Yan; Huang, Congzhi; Cai, Yunfei
Abstract: This paper studies the problems of stability analysis and state feedback stabilization for networked control system. By developing a novel delay-partitioning approach, the information on both the range of network-induced delay and the maximum number of consecutive data packet dropouts can be taken into full consideration. Various augmented Lyapunov–Krasovskii functionals (LKFs) with triple-integral terms are constructed for the two delay subintervals. Moreover, the Wirtinger-based inequalities in combination with an improved reciprocal convexity are utilized to estimate the derivatives of LKFs more accurately. The proposed approaches have improved the stability conditions without increasing much computational complexity. Based on the obtained stability criterion, a stabilization controller design approach is also given. Finally, four numerical examples are presented to illustrate the effectiveness and outperformance of the proposed approaches. Highlights: This paper presents novel stabilization approach for networked control system. Augmented Lyapunov–Krasovskii functionals (LKFs) are constructed to exploit the information of network phenomena. The Wirtinger-based inequalities are utilized to bound the cross terms in derivative of LKFs. Based on the proposed stability criterion, the stabilization controller design approach is also given. Four well-known examples show the reduced conservatism of the obtained results.